Nr4a1-dependent non-classical monocytes are important for macrophage-mediated wound healing in the large intestine - Heidbreder, Karin; Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja M.; Atreya, Imke; Hildner, Kai; Neurath, Markus F.; Zundler, Sebastian (Frontiers in Immunology, 2023)
Macrophages play an important role in intestinal wound healing. However, the trajectories from circulating monocytes to gut macrophages are incompletely understood. Taking advantage of mice depleted for non-classical monocytes due to deficiency for the transcription factor Nr4a1, we aimed to address the relevance of non-classical monocytes for large intestinal wound healing. We show that wound healing in Nr4a1-deficient mice is substantially delayed and associated with reduced peri-lesional presence of macrophages with a wound healing phenotype. Thus, our data suggest that non-classical monocytes are biased towards wound healing macrophages. Our insights might help to understand, how targeting monocyte recruitment to the intestine can be used to modulate intestinal macrophage functions.